An injectable click-crosslinked hyaluronic acid hydrogel modified with a BMP-2 mimetic peptide as a bone tissue engineering scaffold - Park, Seung Hun; Park, Joon Yeong; Ji, Yun Bae; Ju, Hyeon Jin; Min, Byoung Hyun; Kim, Moon Suk (Acta Biomaterialia, 2020)
An injectable, click-crosslinking (Cx) hyaluronic acid (HA) hydrogel scaffold modified with a bone morphogenetic protein-2 (BMP-2) mimetic peptide (BP) was prepared for bone tissue engineering applications. The injectable click-crosslinking HA formulation was prepared from HA-tetrazine (HA-Tet) and HA-cyclooctene (HA-TCO). The Cx-HA hydrogel scaffold was prepared simply by mixing HA-Tet and HA-TCO. The Cx-HA hydrogel scaffold was stable for a longer period than HA both in vitro and in vivo, which was verified via in-vivo fluorescence imaging in real time. BP acted as an osteogenic differentiation factor for human dental pulp stem cells (hDPSCs). After its formation in vivo, the Cx-HA scaffold provided a fine environment for the hDPSCs, and the biocompatibility of the hydrogel scaffold with tissue was good. Like traditional BMP-2, BP induced the osteogenic differentiation of hDPSCs in vitro. The physical properties and injectability of the chemically loaded BP for the Cx-HA hydrogel (Cx-HA-BP) were nearly identical to those of the physically loaded BP hydrogels and the Cx-HA-BP formulation quickly formed a hydrogel scaffold in vivo. The chemically loaded hydrogel scaffold retained the BP for over a month. The Cx-HA-BP hydrogel was better at inducing the osteogenic differentiation of loaded hDPSCs, because it prolonged the availability of BP. In summary, we successfully developed an injectable, click-crosslinking Cx-HA hydrogel scaffold to prolong the availability of BP for efficient bone tissue engineering.
Keywords: Bone morphogenetic protein-2; Bone morphogenetic protein-2 mimetic peptide; Bone tissue engineering; Click-crosslinking; Dental pulp stem cells; Human dental pulp stem cell; Hydrogel scaffolds; Injectable hydrogel scaffold; Injectable hydrogels; Mimetics; Osteogenic differentiation; Humans; Hyaluronic Acid; Hydrogels; Osteogenesis; Tissue Engineering; Tissue Scaffolds; BMP-2 mimetic peptide; Bone tissue engineering; Click-crosslinking; Human dental pulp stem cells; Injectable hydrogel scaffold; Osteogenic differentiation